Understanding the Low Success Rate of Tax Appeals: A Qualitative Case Study Using Fishbone Analysis - Falumi, Verdy Nizar; Rosid, Arifin (E-Jurnal Akuntansi; Vol 35 No 4 (2025)DO - 10.24843/EJA.2025.v35.i04.p14, 2025)
Tax court data indicates an increasing trend in the number of tax disputes. Further analysis of appeal decisions from 2019-2023 within the jurisdiction of the South Jakarta Madya Tax Office I reveals that 47.23% of all decisions resulted in "granting all" verdicts. This outcome demonstrates that the Directorate General of Taxes' (DGT) success rate remains suboptimal. This study aims to identify the causes and potential solutions for the low rate of DGT's success, particularly in the KPP Madya Jakarta Selatan I. The research methodology employs a qualitative case study approach utilising fishbone analysis of data derived from "granting all" appeal decisions and interviews with parties involved in the appeal process. The findings of this study suggest that the DGT's lack of success in tax audits is attributable to disparities in the interpretation of regulatory implementation among tax auditors, taxpayers, and tax courts; the utilisation of indirect methods without corroborating evidence; and the availability of relevant evidence during the audit phase and new evidence during the trial proceedings. Keywords: Tax Audit; Tax Disputes; Tax Appeal; Fishbone Analysis